2-Styrylchromones: Cytotoxicity and Modulation of Human Neutrophils' Oxidative Burst - Mariana Lucas; Marisa Freitas; Marco Zanchetta; Artur M. S. Silva; Eduarda Fernandes; Daniela Ribeiro (MDPI AG, 2022)
Neutrophils are polymorphonuclear leukocytes recruited to sites of acute inflammation, in response to pathogen invasion and tissue injury. The modulation of their activity, especially oxidative burst, may be important to control the inflammatory process. 2-Styrylchromones (2-SC) are derived from chromones and despite their recognized multiple biological activities, their anti-inflammatory and antioxidant properties are still poorly explored. Therefore, in this study, 43 structurally related 2-SC were evaluated concerning their effects on freshly isolated human neutrophils' viability and oxidative burst. The studied 2-SC were divided into eight groups according to their substitution at C-4' on B-ring (none, -OH, -OCH3, -OBn, -CH3, and -NO2), existence and location of -Cl on B-ring, and presence of -Br at C-3 on C-ring. Overall, most of the studied 2-SC did not affect neutrophils' viability, at physiological relevant concentrations. The ones belonging to B group were the most effective (IC50 values < 2 μM), and present one -OH group at C-4' or a catechol group at C-3' and C-4' on B-ring. These substituents seem to play an important role in the modulatory activity of human neutrophils' oxidative burst. These results reinforce the great potential of 2-SC's scaffold for the development of new anti-inflammatory agents.